2019
DOI: 10.3390/nu11122855
|View full text |Cite
|
Sign up to set email alerts
|

The Extra-Virgin Olive Oil Polyphenols Oleocanthal and Oleacein Counteract Inflammation-Related Gene and miRNA Expression in Adipocytes by Attenuating NF-κB Activation

Abstract: Inflammation of the adipose tissue plays an important role in the development of several chronic diseases associated with obesity. Polyphenols of extra virgin olive oil (EVOO), such as the secoiridoids oleocanthal (OC) and oleacein (OA), have many nutraceutical proprieties. However, their roles in obesity-associated adipocyte inflammation, the NF-κB pathway and related sub-networks have not been fully elucidated. Here, we investigated impact of OC and OA on the activation of NF-κB and the expression of molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 122 publications
(158 reference statements)
7
55
0
Order By: Relevance
“…This data suggests that the consumption of EVOO with a high content of OC can have important anti-inflammatory effects, and it is consistent with the natural anti-inflammatory properties of OC [ 14 , 77 , 78 ]. It has been previously reported that one of the mechanisms underlying the anti-inflammatory properties of OC is the inhibition of the nuclear factor-κB (NF-kB) pathway [ 79 ], which in turn may not only reduce the levels of pro-inflammatory cytokines but also attenuate cortical cyclooxygenase-2 (COX-2) signaling [ 80 ]. However, further investigations are needed for a better understanding of this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests that the consumption of EVOO with a high content of OC can have important anti-inflammatory effects, and it is consistent with the natural anti-inflammatory properties of OC [ 14 , 77 , 78 ]. It has been previously reported that one of the mechanisms underlying the anti-inflammatory properties of OC is the inhibition of the nuclear factor-κB (NF-kB) pathway [ 79 ], which in turn may not only reduce the levels of pro-inflammatory cytokines but also attenuate cortical cyclooxygenase-2 (COX-2) signaling [ 80 ]. However, further investigations are needed for a better understanding of this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal overexpression of COX2 has also been shown to be an independent indicator of worse overall survival in breast cancer ( 133 ). Oleocanthal has demonstrated the capacity to downregulate expression of COX2 and activity of NF-kB in adipocytes ( 134 ). Given that the breast stroma is largely populated by adipocytes, this collective evidence suggests the MD could facilitate an intra- and extra-tumoral environment that suppresses the NF-κB/COX2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable antioxidant and anti-inflammatory potential has also been exhibited by oleocanthal, a phenolic compound responsible for the burning sensation at the back of the throat when consuming EVOO [ 81 , 82 ], and by other phenolic compounds [ 83 , 84 ].…”
Section: Effect On General Mechanisms Of Diseasementioning
confidence: 99%